Antipsychotic-induced weight gain - Pharmacogenetic studies - Olajossy-Hilkesberger, L; Godlewska, B; Marmurowska-Michałowska, H; Olajossy, M; Landowski, J (2006)
Drug-naive patients with schizophrenia often present metabolic abnormalities and obesity. Weight gain may be the side effect of treatment with many antipsychotic drugs. Genetic effects, besides many other factors, are known to influence obesity in patients with schizophrenia treated with antipsychotics. Numerous studies of several genes' polymorphisms have been performed. -759C/T polymorphism of 5HT2C gene attracted most attention. In 5 independent studies of this polymorphism the association between T allele with the lower AP-induced weight gain was detected. No associations could be detected between weight gain and other polymorphisms of serotonergic system genes as well as histaminergic system genes. Studies of adrenergic and dopaminergic system have neither produced any unambiguous results. Analysis of the newest candidate genes (SAP-25, leptin gene) confirmed the role of genetic factors in AP-induced weight gain. It is worth emphasising, that the studies have been conducted in relatively small and heterogenic groups and that various treatment strategies were used.